Vaccination with an Ostertagia ostertagi Polyprotein Allergen Protects Calves against Homologous Challenge Infection - Vercauteren, Isabel (American Society for Microbiology, 2004)
As an alternative to antihelminthic drugs, we are exploiting vaccination to control infections with the abomasal nematode Ostertagia ostertagi in cattle. Our focus for vaccine targets is excretory-secretory (ES) products of this parasite. One of the most abundant antigens in larval and adult Ostertagia ES products is a protein homologous to nematode polyprotein allergens. We found that the Ostertagia polyprotein allergen (OPA) is encoded by a single-copy gene. OPA comprises three or more repeated units, and only the 15-kDa subunits are found in ES products. The native antigen is localized in the intestinal cells of third-stage larvae and in the hypodermis and cuticle of fourth-stage larvae and adult parasites. Vaccination of cattle with native OPA (nOPA) in combination with QuilA resulted in protection against Ostertagia challenge infections. The geometric mean cumulative fecal egg counts in the nOPA-vaccinated animals were reduced by 60% compared to the counts in the control group during the 2-month course of the experiment. Both male and female adult worms in nOPA-vaccinated animals were significantly shorter than the worms in the control animals. In the abomasal mucus of vaccinated animals the nOPA-specific immunoglobulin G1 (IgG1) and IgG2 levels were significantly elevated compared to the levels in the control animals. Reductions in the Ostertagia egg output and the length of the adult parasites were significantly correlated with IgG1 levels. IgG2 titers were only negatively associated with adult worm length. Protected animals showed no accumulation of effector cells (mast cells, globular leukocytes, and eosinophils) in the mucosa. In contrast to the native antigen, recombinant OPA expressed in Escherichia coli did not stimulate any protection.